2019
DOI: 10.3390/molecules25010003
|View full text |Cite
|
Sign up to set email alerts
|

Aptamers Chemistry: Chemical Modifications and Conjugation Strategies

Abstract: Soon after they were first described in 1990, aptamers were largely recognized as a new class of biological ligands that can rival antibodies in various analytical, diagnostic, and therapeutic applications. Aptamers are short single-stranded RNA or DNA oligonucleotides capable of folding into complex 3D structures, enabling them to bind to a large variety of targets ranging from small ions to an entire organism. Their high binding specificity and affinity make them comparable to antibodies, but they are superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
166
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(189 citation statements)
references
References 293 publications
0
166
0
Order By: Relevance
“…Previous research has shown that incorporation of the Bn-dU into AS1411 aptamer significantly enhanced the targeting affinity to nucleolin expressing cancer cells [ 35 ]. Substitutions of the 2′-hydroxyl group on the sugar ring by 2′-amino, 2′-fluoro, or 2′-methoxy are the most common chemical modifications of nucleotides to improve nuclease resistance [ 36 ]. 2′-hydroxyl group modified RNAs are highly resistant to ribonuclease degradation because RNA hydrolysis proceeds by the nucleophilic attack of the deprotonated 2′-hydroxyl group on the adjacent phosphodiester bond of sugar-phosphate backbone [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that incorporation of the Bn-dU into AS1411 aptamer significantly enhanced the targeting affinity to nucleolin expressing cancer cells [ 35 ]. Substitutions of the 2′-hydroxyl group on the sugar ring by 2′-amino, 2′-fluoro, or 2′-methoxy are the most common chemical modifications of nucleotides to improve nuclease resistance [ 36 ]. 2′-hydroxyl group modified RNAs are highly resistant to ribonuclease degradation because RNA hydrolysis proceeds by the nucleophilic attack of the deprotonated 2′-hydroxyl group on the adjacent phosphodiester bond of sugar-phosphate backbone [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical composition Nucleic acid (DNA or RNA) Protein Molecular weight 10-50 kDa 140-700 kDa (8) Aptamers have a smaller molecular weight (~20,000 Da vs.~150,000 Da for mAbs) and are easy to penetrate tissues such as tumors when used for therapeutic purposes [27]. The main limitations of aptamers lie in their susceptibility to degradation by nucleases (this can be overcome by aptamer modification and is discussed in Section 4.3 of the text), the difficulty to select aptamers against some targets, and the rapid renal clearance [31]. In theory, aptamers can be produced against any type of targets, from small inorganic and organic molecules to cells and to whole organisms such parasites, but in practical situations, it is sometimes difficult to obtain high-specific and high-affinity aptamers to some targets [32].…”
Section: Aptamers Mabsmentioning
confidence: 99%
“…Among bioaffinity sensors, aptamer-based ones have gained special interest as they have an enhanced efficiency in contrast to antibodies, as they are more stable, easier to bioconjugate and less toxic [ 60 , 61 ]. However, selection process of aptamers is slightly more tedious as selective evolution of ligands by exponential enrichment (SELEX) has to be performed, so that antibodies are still the most chosen option.…”
Section: Electrochemical Biosensors: the Role Of Nanomaterialsmentioning
confidence: 99%